Fans in Ancient Egypt: Iconographic and Contextual Study of Fans in the Predynastic, Old, and Middle Kingdoms - Zaki, Nadra (AUC Knowledge Fountain, 2024)
A variety of fans existed throughout ancient Egyptian history. They had several forms and were made of different materials. They appear in two- and three-dimensional representations, as well as in texts. They relate to royalty and high officials and also feature in domestic settings, both out- and indoors. Fans were used for creating breeze, and providing shade in real life, and also during the journey to the afterlife, where they combined physical and metaphysical protection. Several names were associated with fans, depending on their functions, both in the secular and sacred world. Earlier studies have either generally examined fans or extensively studied the ceremonial fans of the New Kingdom. Using textual and pictorial evidence, this thesis will focus on an iconographic and contextual study of fans in the Predynastic, Old and Middle Kingdoms, a period that witnessed a variety of shapes of fans, which no former scholarship has examined exclusively. The research tackles five aspects related to fans from the Predynastic to the Middle Kingdoms: the different names for the various types of fans, the functions of fans in daily life, the materials of which fans were made from, the manufacturing process of fans, and the symbolic meaning of fans for mortals, both on earth and in the afterlife. This study sheds light on the role of fans in ancient Egypt as well as providing a database of pictorial (and archaeological) evidence involving fans that will be useful for other scholars and for future work on the subject.